Medical and Legal Aspects of Child Sexual Abuse - Enyedy, Andrea; Tsikouras, Panagiotis; Csorba, Roland (My University, 2018)
Background: Very few studies focus on childhood sexual abuse in middle European countries. Aim: The purpose of our study is to describe the medical and legal characteristics of children who experience sexual abuse and explore common features that may result in strategies for prevention. Methods: Between 2000 and 2015, 400 girls and 26 boys under the age of 18, suspected of being sexually abused, visited one of the four hospitals in a Hungarian county. Results: Mean age at onset was 10.81 years for boys, 13.46 years for girls. In 278 cases (65.3%), the perpetrator was known to the victim, and a stranger was suspected in 148 cases (34.7%). In 79 cases (30.7% of boys and 17.7% of girls), a family member was the accused perpetrator. In more than one-third (boys) and in one-fifth (girls) of cases, sexual abuse had occurred on multiple occasions. In the case of boys, child and adolescent sexual abuse (CSA) included oral genital, genital touching and genital to genital contact in 14 cases (53.8%) and anal intercourse in 12 (46.2%) cases. In case of girls, sexual abuse included coitus in 219 (54.8%), oral genital, genital touching, genital to genital contact in 164 (41.0%), anal abuse in 14 (3.5%) cases, physical injury was incurred in 15 cases. Legal proceedings followed the CSA in 205 (48.1%) cases. Conclusion: The results highlight the urgent need to address the issue of sexual abuse in Hungary and minimize its impact. Prevention requires a systematic and lifelong approach to educating children about personal space safety and privacy to reduce vulnerability and is the responsibility of parents and professionals.
A Population-Based Study in a Hungarian County
Keywords: Sexualisierte Gewalt; Sexuelle Belästigung; Kinder; Jugend; Geschlechterdifferenz; Recht; Prävention; 610 Medizin und Gesundheit